The Vitality of the Knowledge of Sanskrit For Buddhism in Southeast Asia* - Sinak, Mr. Sanit (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2018)
Although Pāli was the main language of the southern Buddhist, the knowledge of Sanskrit is necessary to help more understanding Buddhism. As knowing for long time, the southern Buddhism, Theravāda, recorded the Buddha's teachings in Pāli, while the northern, Mahāyāna recorded in Sanskrit language. Studying Sanskrit has taken the important role in many countries which accepted the teachings of Theravāda Buddhism along with Pāli.             To understand the teachings of the Lord Buddha, we need to study the languages which has been recorded them in religious texts, not only Pāli but Sanskrit also. In our present time, difficulty of language makes trouble for people and they turned away. In Southeast Asia, many countries accepted the Buddha's teachings as the religion of mostly people. Therefore, to understanding and to practicing the Buddhism need ability of the languages. Moreover, the relation between Pāli and Sanskrit is very close in many aspects. So the knowledge of Sanskrit is very important to study Buddhism, both Theravāda and Mahāyāna. The Buddhist monks who have important role to spread and protect the right teachings in this global society more need to study and understand the religious languages.             Furthermore, there are many mistakes in interpretation of Buddhist virtues by the person who has not enough knowledge of Pāli and Sanskrit. In the current paper, the objectives are to study about the necessity of Sanskrit for Buddhism in Southeast Asia and Vietnam. to present the significant of knowledge of both Pāli and Sanskrit which being used to understand the Buddhism of the people in this region. Keywords: Sanskrit, Buddhism and Southeast Asia